Is sarcopenia a predictor of prognosis for patients undergoing radiotherapy for head and neck cancer? A meta-analysis. Issue 4 (April 2021) - Findlay, Merran; White, Kathryn; Stapleton, Natalie; Bauer, Judith
Summary: Introduction: Computed tomography (CT)-defined sarcopenia is a demonstrated poor prognostic factor for survival in patients with cancer, however, its impact in patients with head and neck cancer (HNC) has only recently been explored. This study aimed to determine the prognostic impact of CT-defined sarcopenia at the level of the third lumbar vertebra (L3) on overall survival in patients with HNC undergoing radiotherapy ± other treatment modality of curative intent. Methods: A systematic review of the literature published between January 2004 and May 2020 was conducted in Medline, Embase, CINAHL, AMED and PubMed. Empirical studies in adults (≥18 years) who had completed radiotherapy of curative intent ± other treatment modalities that evaluated sarcopenia using the gold standard method at L3 and applied sex-specific cut-offs were included. Outcome of interest was overall survival. Study quality was assessed using the Quality In Prognosis Studies (QUIPS) tool. Hazard ratios with 95% confidence intervals derived from multivariate analysis were extracted directly from studies. Random-effects meta-analysis was used to determine the pooled hazard ratio for overall survival in patients with sarcopenia versus those without using RevMan (Version 5.3). The certainty of evidence was assessed using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) system. Results: A total of 6211 studies were identified and screened from which seven studies met the inclusion criteria with 1059 pooled patients. All studies defined sarcopenia as low muscle mass but varied in skeletal muscle index (SMI) threshold values applied and ethnicity. Sarcopenia prevalence ranged from 6.6 to 64.6% pre-treatment and 12.4 to 65.8% post-treatment. Pre-treatment sarcopenia was associated with reduced overall survival (HR 2.07; 95%CI, 1.47–2.92, p < 0.0001, I 2  = 49%) with similar findings for post-treatment sarcopenia (HR 2.93; 95%CI, 2.00–4.29, p < 0.00001, I 2  = 0%) with moderate to low heterogeneity exhibited amongst studies respectively. The certainty of evidence for overall survival according to GRADE was low for pre-treatment sarcopenia and moderate for post-treatment sarcopenia. Conclusions: CT-defined sarcopenia is independently associated with reduced overall survival in patients with HNC and holds a clinically meaningful prognostic value. Consensus regarding sarcopenia assessment and definitions is warranted in order to substantiate these findings and support implementation of body composition assessment as a clinically meaningful prognostic tool into practice.